The Road From Abstract to Publication in Pediatric Urology - Spencer, Katelyn A.; Levy, Brittany; Martin, Regan; Copeland, Haley; Cranford, Will; McLouth, Christopher; Buchanan, Amanda F. (Urology (Ridgewood, N.J.), 2025)
To identify the current rate of achieving publication and time to publication of abstracts presented at Societies for Pediatric Urology (SPU) meetings. Fall SPU poster and podium presentations from 2017-2019 and 2021 were identified and reviewed for authorship (academic position), institutional (presence of pediatric urology fellowship), and publication (date of publication, journal, impact factor, and changes in authorship) details. Of the 688 abstracts presented at the annual fall SPU meeting, 311 (45.2%) were published, with an average time to publication of 12.3months (standard deviation 10.8months). The academic position of first authors was distributed among medical students (7.5%), residents (20.2%), fellows (28.5%), attendings (28.8%), and others (PhD, RN, etc) (15%), while last authorship was dominated by attending physicians (90.2%). There were no significant author or institutional factors associated with achieving publication or time to publication. However, abstracts presented in 2021, after the canceled 2020 meeting, were published in an average of 6.7months, compared to 14.6months from 2017-2019 (P<.001). While the annual SPU meeting is an important venue for presenting new information, the follow-through to publication is an area for improvement, which may limit dissemination of important new research. It does not appear that any author-specific factors or the affiliation with a fellowship program is associated with ultimate publication of presented abstracts.